Analysis of Economic Vulnerability to Disaster Threats in Batu City - Firre An Suprapto; Bambang Juanda; Ernan Rustiadi; Khursatul Munibah (Universitas Negeri Semarang, 2022)
Geographically, Indonesia is located on three of the world's main tectonic plates and has 127 active volcanoes, making it highly vulnerable to natural disasters. In addition to natural disasters, Indonesia is also facing the Covid-19 disaster, which has greatly affected the tourism sector. Batu City is one of the leading tourism areas. Because Batu City is prone to disasters, this will certainly have an impact on the economy of the people of Batu City. Therefore, this study aims to analyze economic vulnerability due to disasters and the role of institutions in dealing with them. This research is a case study that uses a quantitative and qualitative approach, using the results of respondent interviews, ArcMap 10.3, ILWIS software, and MACTOR. The results obtained are that the disasters that have the most severe impact on the economic vulnerability of Batu City are droughts and earthquakes. In addition, other results also show that the role of institutions has not been good enough in creating institutional strategies in Batu City. Based on the modeling results using MACTOR, it is known that the disaster management efforts carried out by the tourism object and the Regional Apparatus Organization (OPD) agree and support the implementation of these efforts.